2019
DOI: 10.1098/rspb.2019.1948
|View full text |Cite
|
Sign up to set email alerts
|

Variation at an adhesin locus suggests sociality in natural populations of the yeast Saccharomyces cerevisiae

Abstract: Microbes engage in numerous social behaviours that are critical for survival and reproduction, and that require individuals to act as a collective. Various mechanisms ensure that collectives are composed of related, cooperating cells, thus allowing for the evolution and stability of these traits, and for selection to favour traits beneficial to the collective. Since microbes are difficult to observe directly, sociality in natural populations can instead be investigated using evolutionary genetic signatures, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 65 publications
0
24
0
Order By: Relevance
“…For example, associating mat traits, like the pH environment generated by a strain, with the niche from which it was collected may provide insights into which traits are favored under different ecological circumstances. Furthermore, uncovering natural genetic variants that control mat biofilm formation, as has been done for other complex life‐history traits in yeast (De Chiara et al, 2022), or further investigating the biochemical properties of natural FLO11 variants (Oppler et al, 2019) and the conditions under which they generate the greatest cell‐cell adhesion (Bouyx et al, 2021; Brückner et al, 2020) could provide insight into the molecular basis of how multicellularity is favored in this organism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, associating mat traits, like the pH environment generated by a strain, with the niche from which it was collected may provide insights into which traits are favored under different ecological circumstances. Furthermore, uncovering natural genetic variants that control mat biofilm formation, as has been done for other complex life‐history traits in yeast (De Chiara et al, 2022), or further investigating the biochemical properties of natural FLO11 variants (Oppler et al, 2019) and the conditions under which they generate the greatest cell‐cell adhesion (Bouyx et al, 2021; Brückner et al, 2020) could provide insight into the molecular basis of how multicellularity is favored in this organism.…”
Section: Discussionmentioning
confidence: 99%
“…The strains used in this study represent a range of colony phenotypes observed on low agar medium (Hope and Dunham, 2014; Oppler et al, 2019; Regenberg et al, 2016). Unlike when studying a single genetic background in which biofilm and “smooth” mats can be easily differentiated, the phenotype is continuous in environmental isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, expression of a number of Flo11A domains from diverse Saccharomycetales species in an S. cerevisiae model has shown that the capacity of these adhesins for conferring cell-cell adhesion through homotypic interactions is highly conserved (Brückner et al 2020). These studies have further shown that Flo11-type adhesins can act as cell surface receptors, which mediate kin discrimination in mixed S. cerevisiae populations that express variants from different species or sub-species (Brückner et al 2020;Oppler et al 2019). In addition, Flo11 adhesins confer competitive advantages through cell differentiation in clonal biofilms (Regenberg et al 2016).…”
Section: Flo11-type Adhesinsmentioning
confidence: 99%
“…Flo11p harbors a fibronectin type III-like domain that confers homophilic protein-protein interaction with neighbouring cells 11,21 . Flo11p-mediated ad-hesion partakes in multiple ST group phenotypes such as biofilm 11,22 and pseudohyphae formation 23 . In contrast, the FLO1 gene encodes for a PA14-like N-terminal domain that binds to mannose residues on the cell wall of neighbouring cells, a mechanism that is heterophilic in nature 24,25 .…”
Section: Introductionmentioning
confidence: 99%